Pengembangan Keterampilan Kerja Melalui Kegiatan Magang di Kementerian Kebudayaan Republik Indonesia - Cinta Pradana; Andara Liluyani; Virliana Amanda; Hesti Kusumaningrum (CV. ITTC INDONESIA, 2026)
One type of experience-based learning called an internship aims to improve students' abilities through direct involvement in the world of work. This article will explain how internships are carried out by students of the Education Management Study Program at the Ministry of Culture of the Republic of Indonesia and analyze how internships contribute to improving student abilities. The method used is a descriptive qualitative approach that uses data collection techniques through observation, documentation, and literature study. The results of the activities show that students are actively involved in administrative tasks such as data management, documentation, and work coordination. This indicates that students can apply their theories to the real world. Internships improve students' soft skills, such as responsibility, discipline, communication, and teamwork, in addition to improving their technical skills. Although there are several operational obstacles related to infrastructure, filing systems, and work coordination, adjustments have been made to reduce these problems.